â€œHer Flowers are Her Childrenâ€: Cultivating Victorian Houseplant Motherhood in Colonial Archives - Garascia, Ann (Journal of Ecohumanism, 2023)
This essay introduces the figure of Victorian â€œplant motherâ€ whose houseplant amities provide an alternative model of motherhood within nineteenth-century colonial archives. I argue that compiling instances of her dispersed presences across archival documents reveals a flexible avatar of motherhood who restores maternityâ€™s embodied and emotional dimensions. Not simply an agent of colonialism, the plant mother and her plants provide moments of transformation that coax out of colonial archival structures more inclusive models of domesticity, family, and belonging. To access these moments, I build a framework for interpreting nineteenth-century archival materials that braids feminist and critical plant studies perspectives that share commitments to expanding understandings of archives in their theoretical and material forms. This essay reconstructs the lives of Victorian plant mothers from plant births to deaths. Through these archival reconstructions, I insist that Victorian houseplant mothers show us how to locate nodes of loving resistance within colonial archival structures.